THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING ENGLISH AT THE FIRST YEAR OF SMA NEGERI 1 GABUS-GROBOGAN IN 2010/2011 ACADEMIC YEAR - HANDOKO, ARI (2011)
The objective of the research is to describe the implementation of Genre-Based Approach (GBA) in the teaching of English. Besides, it was also conducted to study the procedures of the process of teaching English using genre-based approach, the activities used in teaching English applying Genre-based Approach, the problems in implementing of GBA, and the way used by the teachers to overcome the problem in implementing the GBA in the process of teaching English. In this research, the writer uses descriptive qualitative research which describes the implementation of Genre-based Approach in teaching of English. The data comprise activities in teaching of English, information from English teacher, and students in SMA N 1 Gabus, Grobogan. The methods of collecting are observation, interview and documentation. The procedures for analyzing data are reducing, display, and verification. The result shows that the teacher uses four procedures in teaching English using GBA, namely (BKOF), (MOT), (JCOT), and (ICOT). The writer finds also that there are two patterns in teaching English using GBA. In the first patterns the teacher uses four procedures and in the second patterns the teacher only uses three procedures, namely (BKOF), (MOT), and (ICOT). In every stage, there are many activities in classroom done by the teacher. The activities in BKOF are asking question and giving explanation. In MOT the teacher gives the same text to discuss. In JCOT, the activity is making group. And the activities in ICOT are giving the task in the classroom and giving task as homework.